Die Waardes, Verwagtings en Bevredigings van Suid-Afrikaanse T elevisienuuskykers - Linda Venter; Nina Overton (Communicare)
THIS Investigation examines the audience experience with television news in South Africa and presents a process model of uses and gratifications based upon an expectancy-value approach. The prime objective was accomplished when three reliable scales for the measure ment of values attached to television news Items; expectations about finding such news-items; and gratification of these ex pectations were developed. A significant correlation between all three scales was in dicated, although the correlation between values and expectations was much stronger than the correlation between values and gratifications. While the correlation between expectations and gratifications was still significant, it was also much lower than the correlation between values and expecta tions. This finding provides evidence against the criticism that since a gratification is ex pected and sought, it must necessarily be obtained. Instead, it is found that television news programmes in South Africa, while ef fective, are imperfect providers of news related gratifications sought. To cast addi tional light on the relative lower correlation between expectations and gratifications, the degree of dependence on television news as primary source was taken into ac count.